(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the long-term clinical and radiographic outcomes, as well as the implant success rate, of immediate implant placement after a 5-year follow-up period. Materials and Methods: A retrospective study was conducted on patients who underwent immediate implant placement following tooth extraction at 108 Military Central Hospital between 2015 and 2021. A total of 112 implants were placed, of which 83 implants in 64 patients were followed for a minimum of 5 years. Gingival–bleeding index, plaque index, probing depth, and marginal bone loss around the implants were periodically assessed from 6 months to 5 years after prosthetic loading in accordance with the Albrektsson success criteria. Results: Peri-implant soft tissue health was maintained over time, with early improvements in plaque index and probing depth. Marginal bone loss increased gradually over time but remained within physiologically acceptable limits after 5 years. The implant success rate at 5 years was 88.0%, and the implant survival rate was 94,6%. Conclusion: Immediate implant placement demonstrates favorable long-term outcomes, meets the Albrektsson criteria for implant success, and represents a safe and effective treatment modality in clinical practice.